Lessons From The Molecular Biology Of Neonatal Hyperbilirubinaemia. - H., Van Rostenberghe; H., Nishio; M., Matsuo; R., Noraida; W.I., Wan Pauzi

(untitled)
Neonatal jaundice is the most common condition requiring medical attention in the newborn period. It has been classically attributed to a number of more or less common causes. The causes are classically divided in two main groups. The first group is comprising of conditions associated with an increase in break down of red blood cells such as Rhesus incompatibility, ABO blood group incompatibility, G6PD deficiency, birth trauma and polycythaemia. A second group consists of conditions in which the excretion of bilirubin is diminished such as breast feeding jaundice, breast milk jaundice, Gilbert syndrome or the more severe Crigler Najjar syndrome. Many babies however get jaundice.